Components of Mathematical Proficiency Included in the Second Intermediate Grade Mathematics Book (Journal of the College of Basic Education, 2022)
The current research aims to analyze the content of the second intermediate grade mathematics book according to the components of mathematical proficiency. The researcher used the descriptive analytical method for its relevance to the nature of the objectives of the study، as she analyzed the content of the book according to the components of mathematical prowess: conceptual comprehension، procedural fluency، strategic efficiency، and adaptive reasoning. And by using frequency and percentages، and (Holsti) equation to calculate the stability of the analysis between the researcher and herself over time، and between her and another researcher. The research found that the content of the mathematics book for the second intermediate grade focused on: conceptual comprehension، procedural fluency، adaptive reasoning، and strategic efficiency accordingly. And holding training courses for mathematics teachers during the service، through which they increase their awareness of the importance of analyzing the mathematical material they study according to the components of mathematical proficiency. The researcher suggested some suggestions، including a study to find out the extent to which mathematics teachers possess mathematical prowes